Impacts of extreme heat on mental health: Systematic review and qualitative investigation of the underpinning mechanisms - Lea Baecker; Udita Iyengar; Maria Chiara Del Piccolo; Andrea Mechelli (The Journal of Climate Change and Health)
Introduction: We are living on an increasingly hot planet, with negative impacts for the mental health of affected individuals and communities. A better understanding of the physiological, psychological, behavioral, and social mechanisms which underlie these impacts could inform the development of effective interventions. Here, we conducted a mixed-method study combining a systematic review and qualitative investigation to explore these mechanisms. Methods: Adhering to the PRISMA guidelines, we searched PubMed for publications related to extreme heat, mental health, and mechanisms. Peer-reviewed studies reporting original data on mechanisms explaining the impact of extreme heat on mental health were included. In addition, we conducted six focus groups on extreme heat and mental health with a total of 33 participants (n = 21 people with lived experience, n = 12 healthcare professionals). Transcripts were analyzed using thematic content analysis. Results: Out of 241 articles identified by the literature search, four studies were eligible for inclusion. These provided limited evidence for activation of the hypothalamic-pituitary-adrenal axis, increased psychological stress, reduced exercise, and sleep disruption. The analysis of the focus groups expanded these findings by highlighting additional themes related to physical (e.g., fatigue), psychological (e.g., health anxiety), behavioral (e.g., reduced access to usual coping strategies), and social mechanisms (e.g., social isolation). Conclusion: There is a dearth of reliable data on the mechanisms underpinning the impacts of extreme heat on mental health. Our mixed-method approach identified a range of promising physiological, psychological, behavioral, and social mechanisms, and highlights the importance of including people with lived experience in the conversation.